From Celebration to Empowerment: A Synergistic Model of Community, Culture, and MSMEs in the Cisarua Bisa Festival 2025 - Gunawan, Wawan; Sutono, Anang; Nugroho, Fajar Aditya (Politeknik Negeri Bandung, 2025)
Cultural festivals are increasingly recognized as strategic vehicles for community empowerment and the enhancement of local tourism economies. The Cisarua Bisa 2025 Festival combines three main pillars—community participation, arts and culture, and Micro, Small, and Medium Enterprises (MSMEs)—into a synergistic ecosystem. This study examines how festivals can foster sustainable collaborative models that function as instruments for social empowerment, cultural preservation, and creative economic development. A descriptive qualitative method was employed, involving 21 key informants selected through purposive sampling, with data collected over three days through participant observation, in-depth interviews, documentation analysis, and literature review. The findings reveal the emergence of the Festival-Based Community Empowerment Model (FBCEM), which emphasizes integrated community engagement, cultural heritage preservation, and MSME development. This model contributes a novel conceptual framework that is replicable in other regions. Academically, the research enriches the discourse on cultural tourism and empowerment models; practically, it offers strategic insights for stakeholders aiming to develop festivals as sustainable and collaborative platforms.